Integration of Information Literacy into the Primary Education Curriculum: A Study of Elementary School Libraries in Enrekang Regency - Andi Ahmad Chabir Galib; Ismaya Ismaya; Syawal Syawal; Elihami Elihami (Universitas Muhammadiyah Enrekang, 2024)
The rapid development of information technology demands that learners acquire information literacy skills from an early age as part of 21st-century competencies. Information literacy encompasses not only the ability to search for and use information but also the skills to evaluate, process, and present information critically and ethically. In the context of primary education, the curriculum and school library play a strategic role in laying the foundation for information literacy from an early stage. This study aims to explore how the integration of information literacy into the primary education curriculum is implemented in elementary schools in Enrekang Regency, as well as how school libraries contribute to supporting this process. The research employs a descriptive qualitative approach using a case study method in three elementary schools that have active library programs. Data collection was conducted through in-depth interviews with teachers, librarians, and principals; observation of literacy activities; and document analysis (lesson plans, syllabi, and library programs). The findings indicate that the integration of information literacy remains incidental and is not yet structured within the formal curriculum. School libraries have made efforts to become open learning spaces, yet their role has not been fully optimized due to limited resources and coordination among school stakeholders. The implication is that supportive policies are needed to systematically strengthen information literacy through curriculum integration, teacher training, and the revitalization of school libraries as literacy centers and learning resource hubs.